Gambaran Determinan Kematian Ibu di Kota Surabaya Tahun 2015-2017 - Hazar Rochmatin (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
Maternal mortality rate is one of indicator in assessing the welfare of the community in a region. The high level of Maternal Mortality Rate is a low level signals of public health. Data on maternal mortality in the city of Surabaya shows a decrease in the last 6 years from 144.66 in 2012 to 79.40 in 2017. Although it has shown a decline in progress, this figure still puts Surabaya as the second largest contributor to maternal deaths in East Java in 2017. The study aims to describe the determinants of maternal mortality in Surabaya based on contextual, intermediate and proxy determinants for 2015-2017. This research is descriptive by using secondary data in the form of recapitulation of Maternal Verbal Autopsy (OVM) data on maternal deaths at Surabaya City Health Office The results showed that based on education, the majority of mothers who died had secondary education of 52.29% (57 people). Based on work, the majority of mothers have jobs as housewives of 68.81% (75 people). Based on the age of the mother, the majority of deaths occurred in women aged 20-34 years with a percentage of 66.97% (73 people). According to parity, the majority of mothers who died occurred during pregnancy of the second child by 31.19% (34 people). Based on the period of death, the majority occurred in the puerperium with a percentage of 66.97% (70 people). According to the cause of single death, the majority of maternal deaths were caused by pre-eclampsia/eclampsia with a percentage of 26.61% (29 people). This study recommends the need for early recognition of mothers about antenatal care and danger during pregnancy, childbirth and the puerperium period and increased alertness of health workers to complications of pregnancy, especially in mothers with a history of disease.